Post-Colonial Approaches in Kazakhstan and Beyond
XIII, 217 p. 11 illus., 10 illus. in color.
Keywords: This book explores the postcolonial discourse and decolonization processes in modern Kazakhstan and beyond. It pays particular attention to such areas as national and religious identity, language, literature, and historical narratives. Despite the fact that the post-colonial theory initially emerged in other regions of the world, it has increasingly been applied in the scholarship on Central Asia. Exploring recent debates on post-coloniality in Kazakhstan, this book is an attempt to bring together two bodies of scholarly literature: scholarship on culture and society in post-Soviet Central Asia and research on post-colonial theory. This volume will be of interest to scholars of Eurasian studies as well as researchers and students of post-colonialism in various contexts beyond Eurasia. Dina Sharipova is an Associate professor at the Graduate School of Public Policy at Nazarbayev University in Astana. Her research interests include nation and state-building, security issues, formal and informal institutions, civil society, and well-being in Central Asia. Dr. Sharipova is the author of the book “State-building in Kazakhstan: Continuity and Transformation of Informal Institutions”, Lexington Books, 2018. She has published in Europe-Asia Studies Journal, Nationalism and Ethnic Politics, Central Asian Survey, Nationalities Papers, and in other scholarly journals. Alima Bissenova is an Associate Professor of Anthropology at Nazarbayev University. She specializes in urban anthropology, anthropology of Islam, postcolonial studies, and intellectual history. She has published her work in English and Russian in the journals Religion, State, and Society, Europe-Asia Studies, AB Imperio, Novoe Literaturnoe Obozrenie, Sotsiologiya Vlasti. Aziz Burkhanov is an Associate Professor at the Graduate School of Public Policy at Nazarbayev University in Astana, Kazakhstan. His research interests include nationalism and identity theories, and national identity politics, policies, and practices, with a special focus on identity issues and their perceptions in the public narratives in the former Soviet area. Dr. Burkhanov has published his work in Cornell International Law Journal, Nationalism and Ethnic Politics, and Ethnic and Racial Studies, among others.